Multi-instrument Search for Gamma-Ray Counterpart of X-Ray Transients Detected by EP/WXT - Zhang, Yan-Qiu; Xue, Wang-Chen; Zhang, Jin-Peng; Cai, Ce; Xiong, Shao-Lin; Li, Cheng-Kui; Liu, Yuan; Wang, Chen-Wei; Guo, Hao-Xuan; Xiao, Shuo; Tan, Wen-Jun; Zheng, Chao; et al. (Astrophysical journal. Letters, 2025)
As a soft X-ray imager with an unprecedentedly large field of view, Einstein Probe (EP)/Wide-field X-ray Telescope (WXT) has detected many (fast) X-ray transients, whose nature is very intriguing. Whether there is a gamma-ray counterpart for the X-ray transient provides important implications for its origin. Some of them have been reported to be associated with gamma-ray bursts; however, a systematic study on the gamma-ray emission of these X-ray transients is lacking. In this work, we implemented a comprehensive targeted search for gamma-ray counterparts to 63 X-ray transients reported by EP/WXT during its first year of operation, using the dedicated multiple-instrument search pipeline, Energetic Transients Joint Analysis System for Multi-Instrument (ETJASMIN), with GECAM-B, GECAM-C, Fermi/GBM, and Insight-HXMT data. We find that 14 out of 63 (22%) EP/WXT X-ray transients have gamma-ray counterparts. For other transients, the ETJASMIN pipeline provided the upper limit of the gamma-ray emission, which is more stringent than that given by an individual instrument. Moreover, we investigated the properties of the X-ray transients and their gamma-ray counterparts and explored the relation between the X-ray transient and the gamma-ray counterpart.